A Model for Protecting the Right to Education for Child Labour - Yana Suryana; Yulia Kurniaty; Aroma Elmina Martha (Fakultas Hukum Universitas Islam Indonesia, 2023)
This study discusses the threat of working children's right to education. The aim of this research is to identify the regulation of working children in Indonesian laws and regulations and to find an ideal model of protecting the right to education for working children. The method used is normative legal research. Researchers conducted a study of legislation to see the synchronization between legislation. Human rights theory and statutory theory are used as analytical tools to examine research results. The results of this study conclude that first, the government has protected children's rights as stipulated in several laws and regulations. There are clear provisions regarding the rights of working children. Second, the right ideal model to protect the educational rights of working children is to use a circle of protection. The circle of protection is a circle of protection for working children so that their right to education is fulfilled. In the circle of protection there are parties that protect working children, namely the government, parents, employers, and the community.Keywords: Children; Work; Protection; Education AbstrakPenelitian ini membahas tentang anak yang bekerja terancam hak pendidikannya.Tujuan dari penelitian ini adalah mengetahui pengaturan anak yang bekerja dalam peraturan perundang-undangan di Indonesia dan menemukan model ideal perlindungan hak pendidikan bagi anak yang bekerja. Metode penelitian yang akan digunakan adalah penelitian hukum normatif. Peneliti melakukan kajian perundang-undangan untuk melihat sinkronisasi antar perundang-undangan. Teori hak asasi manusia dan teori perundang-undangan digunakan sebagai pisau analisis untuk mengkaji hasil penelitian. Hasil penelitian ini menyimpulkan, pertama, Pemerintah telah melindungi hak-hak anak sebagaimana diatur dalam beberapa peraturan perundang-undangan. Ada ketentuan yang cukup jelas terkait hak anak yang bekerja. Kedua, Model ideal yang tepat untuk melindungi hak pendidikan anak yang bekerja adalah menggunakan circle of protection. Circle of protection adalah lingkaran perlindungan bagi anak yang bekerja agar hak pendidikan tetap terpenuhi. Dalam circle of pretection terdapat pihak-pihak yang melindungi anak yang bekerja, yaitu pemerintah, orang tua, pengusaha, dan masyarakat.Kata-kata Kunci: Anak; Bekerja; Perlindungan; Pendidikan